Postawy wobec integracji społecznej osób z niepełnosprawnością w kontekście zmiany pokoleniowej - Kazanowski, Zdzisław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Artykuł prezentuje wyniki analizy akceptacji osób z niepełnosprawnością. W badaniach uczestniczyło 313 osób reprezentujących trzy grupy pokoleniowe. Wyniki badań ujawniły istotną rolę przynależności do grupy pokoleniowej w deklarowaniu akceptacji osób z niepełnosprawnością.

The article presents the results of the analysis related to the social acceptance of people with disabilities. A total of 313 people, representing three generational groups, participated in the study. The research results revealed the important role of belonging to a generational group when declaring acceptance of people with disabilities.
Attitudes Towards the Social Integration of People with Disabilities in the Context of Generational Change
Keywords: akceptacja osób z niepełnosprawnością; pokolenie; postawa; acceptance of people with disabilities; generation; attitude